EURECA - The future of cryogenic dark matter detection in Europe - Kraus, H; Henry, S; Imber, J; Ingleby, S; Malek, M; McGowan, R; Mikhailik, V; Bavykina, I; Bento, A; Hauff, D; Huff, P; Kiefer, M; et al. (2008)
European Underground Rare Event Calorimeter Array (EURECA) will be an astro-particle physics facility in the Laboratoire Souterrain de Modane, aiming to directly detect galactic dark matter. The EURECA collaboration unites CRESST, EDELWEISS and the Spanish-French experiment ROSEBUD, thus concentrating and focussing effort on cryogenic detector research in Europe into a single facility. The aim is to explore WIMP - nucleon scalar cross sections in the 10 - 10 picobarn region with a target mass of up to one ton. A major advantage of EURECA is the planned use of more than just one target material (multi target experiment for WIMP identification).